3-Acetyl-1-(2,6-dimethylphenyl)thiourea - Sharatha Kumar; Sabine Foro; B. Thimme Gowda (Acta Crystallographica Section E, 2012)
In the title compound, C11H14N2OS, the two N—H bonds are anti to each other and one of them is anti to the C=S and the other is syn. Further, the amide C=S and the C=O groups are anti to each other. The dihedral angle between the benzene ring and the side chain is 83.74 (5)°. An intramolecular N—H...O hydrogen bond occurs. In the crystal, molecules are linked into inversion dimers by pairs of N—H...S interactions.